New Destination Development and Promotion-India-Importance - Patwardhan, Saurabh (2009)
The tourism industry in India is on the upswing, with major investments made into India and with the changing trends in consumption patterns, it is essential to develop new destinations in India. In order to bridge the gap between demand and supply, it is essential to create a product which the consumers today want. This study focuses on understanding the factors which make a tourist destination successful in India. The research looks upon available research in the field of destination development, tourist motivation and tourist consumption and behaviour. The study is particularly focussed on India. In order to determine the answer to the research question, the study uses qualitative research as its main tool for data collection. Face to face Interviews were carried out, which were later analyzed and interpreted using manual qualitative techniques,written responses were also taken from respondents. The data was collected from two pools of respondents, one being the travel agents and the other potential tourists. Further the implications and limitations of study also have been proposed.